2014
DOI: 10.1212/wnl.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Systemic metabolism in frontotemporal dementia

Abstract: Both patients with bvFTD and those with SD have increased triglyceride and insulin levels and lower HDL cholesterol levels compared with controls, suggesting a state of peripheral insulin resistance. These factors have been found to affect prognosis in motor neuron disease favorably, although insulin resistance has been proposed as a mechanism promoting neurodegeneration. We discuss the potential role of metabolism in FTD pathophysiology and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 41 publications
4
67
0
Order By: Relevance
“…28 One previous study 11 in FTD has suggested that elevated AgRP in CSF may be related to TDP-43 pathology, a finding likely driven by the numbers of patients with svPPA within that cohort; however, this study did not examine the relationship of this peptide to eating behavior or effect on BMI. The current study points toward an important role of AgRP in the eating abnormalities and metabolic changes 4 possibly by promoting hyperphagia, particularly affecting BMI. This provides a potential avenue of research to target this peptide through the use of biological agents.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…28 One previous study 11 in FTD has suggested that elevated AgRP in CSF may be related to TDP-43 pathology, a finding likely driven by the numbers of patients with svPPA within that cohort; however, this study did not examine the relationship of this peptide to eating behavior or effect on BMI. The current study points toward an important role of AgRP in the eating abnormalities and metabolic changes 4 possibly by promoting hyperphagia, particularly affecting BMI. This provides a potential avenue of research to target this peptide through the use of biological agents.…”
mentioning
confidence: 65%
“…Decreased ghrelin and cortisol levels, as well as high insulin levels, have been previously reported in bvFTD. 5 Insulin levels, however, were not related to BMI, which could reflect a state of insulin resistance and metabolic change, 4 rather than a role in controlling satiety. High leptin levels were also observed in a small subset of patients with bvFTD (n 5 5) who overate.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Traditionally frontotemporal dementia (FTD) has been viewed as a syndrome characterized by behavioural and cognitive changes, although increasingly it is being recognized that there is involvement of networks that affect physiological processing including somatosensory processing including pain and temperature (Fletcher et al, 2015a, b), autonomic processing (Ahmed et al, 2015a;Guo et al, 2016), and neuroendocrine and metabolic changes (Ahmed et al, 2014b(Ahmed et al, , 2015b. In behavioural variant frontotemporal dementia (bvFTD), eating behavioural changes are common, including hyperphagia, increased sweet preference and changes in food preference that may be associated with increased body mass index (BMI), dyslipidaemia and insulin resistance (Ahmed et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%